Afatinib with subsequent surgery in stage III NSCLC with EGFR mutation: Lessons learned from two clinical experiences. Issue 6 (December 2018) - Mazzoni, Francesca; Petreni, Paolo; Perna, Marco; Scotti, Vieri; Bongiolatti, Stefano; Livi, Lorenzo; Di Costanzo, Francesco; Voltolini, Luca
Afatinib, a second-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, is effective as first-line treatment in patients with EGFR-mutated non-small cell lung cancer (NSCLC). We report 2 cases of EGFR-mutated locally advanced NSCLC treated in neoadjuvant setting with EGFR tyrosine kinase inhibitor at University of Florence/Careggi Hospital. In both cases, afatinib was used for up to 3 months, until 1 week before surgery. Both patients achieved significant reduction (downstaging) of the pulmonary mass and lymphadenopathies and after surgery, it was decided for both cases to restore afatinib treatment up to a further 4 months. Both patients experienced local and distant disease relapses after 9 and 10 months, respectively, and then we restored the afatinib treatment.